Design of procedures for rare, new or complex processes: Part 1 – An iterative risk-based approach and case study. (December 2017) - Gerbec, Marko; Balfe, Nora; Leva, Maria Chiara; Prast, Steve; Demichela, Micaela
Graphical abstract: Highlights: Approach for the analysis and planning of rare, complex safety critical tasks. Iterative use of task analysis, 4D simulation, hazard analysis and Pareto methods. Demonstrated in a case study on rare water pressure testing of LPG storage tanks. The initial total estimated time was reduced from 30 to 15.3 and next to 14.6 days. The approach was found valuable for detailed planning of critical tasks. Abstract: The paper describes a proposed approach for operationalizing the Common Operational Picture concept introduced in the EU FP 7 TOSCA (Total Operations Management for Safety Critical Activities) project, in order to jointly integrate and enhance safety, quality and productivity in the production environment. The approach combines different methods for the description and analysis of plant and operations, including Task Analysis, 4D process simulation, hazard analysis and Pareto optimization, and iterates through them to generate a final procedure. The proposed approach has been demonstrated on an industrial case study related to planning of infrequent cold water pressure testing of LPG storage tanks, and the process and results of this case study are presented and discussed. The plant management was provided with a detailed list of the main tasks (22), sub-tasks (115), the specific risks identified (26, considering procedural delays, occupational safety and process safety) and the specific recommendations (20) for safety and time optimization of the planned testing procedure. The approach was successfully demonstrated as a suitable vehicle for the analysis and planning of rare, complex, unconventional work tasks that are hard to visualize, where the establishment of a Common Operational Picture (COP) among all relevant personnel in the hazardous operations is a must.